Detection and In Vivo Validation of Dichorhavirus e-Probes in Meta-Transcriptomic Data via Microbe Finder (MiFi®) Discovers a Novel Host and a Possible New Strain of Orchid Fleck Virus - Avijit Roy; Jonathan Shao; Andres S. Espindola; Daniel Ramos Lopez; Gabriel Otero-Colina; Yazmín Rivera; Vessela A. Mavrodieva; Mark K. Nakhla; William L. Schneider; Kitty Cardwell (Viruses)
Dichorhavirus is a recently accepted plant virus genus within the family Rhabdoviridae. Species assigned to the genus consist of bi-segmented, negative sense, single-stranded RNA viruses and are transmitted by Brevipalpus spp. Currently, there are five recognized species and two unclassified members in the genus Dichorhavirus. Four out of seven-orchid fleck virus (OFV), citrus leprosis virus N, citrus chlorotic spot virus, and citrus bright spot virus-can infect citrus and produce leprosis disease-like symptoms. The E-probe Diagnostic for Nucleic Acid Analysis (EDNA) was developed to reduce computational effort and then integrated within Microbe-Finder (MiFi®) online platform to design and evaluate e-probes in raw High Throughput Sequencing (HTS) data. During this study, Dichorhavirus genomes were downloaded from public databases and e-probes were designed using the MiProbe incorporated into the MiFi® platform. Three different sizes of e-probes, 40, 60, and 80 nucleotides, were developed and selected based on whole genome comparisons with near-neighbor genomes. For curation, each e-probe was searched in the NCBI nucleotide sequence database using BLASTn. All the e-probes that had hits with non-target species with ≥90% identities were removed. The sensitivity and specificity of Dichorhavirus genus, species, strain, and variant-specific e-probes were validated in vivo using HTS meta-transcriptomic libraries generated from Dichorhavirus-suspected citrus, orchid, and ornamentals. Through downstream analysis of HTS data, EDNA not only detected the known hosts of OFV but also discovered an unknown host leopard plant (Farfugium japonicum), and the possible existence of a new ornamental strain of OFV in nature.